2023
DOI: 10.3390/molecules28166127
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in C–H Functionalisation through Indirect Hydrogen Atom Transfer

Filip S. Meger,
John A. Murphy

Abstract: The functionalisation of C–H bonds has been an enormous achievement in synthetic methodology, enabling new retrosynthetic disconnections and affording simple synthetic equivalents for synthons. Hydrogen atom transfer (HAT) is a key method for forming alkyl radicals from C–H substrates. Classic reactions, including the Barton nitrite ester reaction and Hofmann–Löffler–Freytag reaction, among others, provided early examples of HAT. However, recent developments in photoredox catalysis and electrochemistry have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 366 publications
0
3
0
Order By: Relevance
“…Hydrogen atom transfer (HAT) is an elementary step in radical chemistry and also a fundamental step involved in many biological systems . Thanks to the rapid development of photocatalysis in the past decade, HAT reactions have found widespread applications in organic synthesis and material science.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atom transfer (HAT) is an elementary step in radical chemistry and also a fundamental step involved in many biological systems . Thanks to the rapid development of photocatalysis in the past decade, HAT reactions have found widespread applications in organic synthesis and material science.…”
Section: Introductionmentioning
confidence: 99%
“…The HAT process involves the abstraction of a hydrogen atom from a substrate using a hydrogen atom abstractor, which is typically a radical species. [27] The choice of a hydrogen atom abstractor has a definitive influence on the efficiency and selectivity of the process. [28][29][30] Thus, the development of a novel hydrogen atom abstractor could provide a dramatic expansion in synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced methods to degrade waste polymers are sustainable alternatives to thermal methods. , Photochemical treatment of synthetic and natural waste polymers has recently become the main focus of scientists because of the lower energy requirements and greener nature, which meet the criteria of sustainability. , Although hydrogen atom transfer (HAT) reactions have always been a versatile tool for C–H bond chemistry, exploitation of light-induced HAT reactions for the degradation/valorization of waste polymers through oxidative C–C bond breakages has recently proved to be an effective and sustainable strategy. Moreover, recent photochemical studies have also demonstrated that halogen radicals can act as the HAT reagent and selectively abstract benzylic hydrogens under mild reaction conditions. , …”
Section: Introductionmentioning
confidence: 99%